Improvement First year vocational college students’ Thai speaking skills for introducing Tourist Attractions - Kunming with Flipped Classroom Teaching Methods - Pu, Xingxue; Buakhieo, Sarita; Chimmode, Songrid (Journal for Developing the Social and Community, 2026)
Background and Aims: This study investigated the effectiveness of flipped classroom teaching methods in improving Thai speaking skills among first-year vocational college students majoring in Thai language. The research focused on students’ ability to introduce tourist attractions in Kunming, addressing the limitations of traditional lecture-based instruction that emphasizes theoretical knowledge over practical communication skills. The study aimed to examine whether the flipped classroom approach could significantly enhance students’ speaking skills and to explore student satisfaction with this innovative teaching model. Methods: A one-group pre-test and post-test experimental design was employed with 30 first-year students from Yunnan Economic Trade and Foreign Affairs Vocational College. The intervention consisted of four 90-minute flipped classroom sessions conducted over one month in the second semester of 2025. Research instruments included lesson plans, video clips, Thai speaking pre-tests and post-tests, and satisfaction questionnaires. Firstly, study relevant theoretical concepts, consult with the thesis advisor, and make revisions as recommended;next adjust according to experts’ suggestions. Finally, actual research was conducted from November to December. Flipped classroom teaching methods lesson plans follow a progressive path of "basic input → situational application → cultural deepening → comprehensive output." Each lesson includes "pre-class preparation (10-minute video + exercises) + 90 minutes of in-class interaction." The video clips consist of four 10-minute pre-class videos, covering vocabulary, sentence patterns, and cultural elements related to introducing Kunming’s tourist attractions. In-class activities emphasized interactive tasks, including role-plays, group discussions, and scenario-based simulations. Data were collected through: (1) a basic test of Thai for tourist-attraction introductions (50 points); (2) a Thai speaking test rated by two independent Thai teachers using a four-dimension rubric (12 points); and (3) a student satisfaction questionnaire with 20 items across six dimensions using a 5-point Likert scale. Statistical analyses included the mean (M), standard deviation (SD), minimum and maximum values, paired-samples t-tests, and Pearson’s product-moment correlation coefficient. Results: Students’ improvement in speaking scores and very high student satisfaction were observed after the flipped classroom intervention. The details are as follows: The Basic Test total score is 50 points, and the mean score of the Basic Test increased from 28.63 (SD = 6.85) in the pre-test to 46.47 (SD = 2.52) in the post-test (t = 14.84, p < 0.001). The speaking test total score improved from 6.53 (SD = 0.54) to 10.20 (SD = 0.69) out of 12 points. All four dimensions showed significant gains, the total score is 3 points. The content completeness (1.67 to 2.57), vocabulary and grammar (1.67 to 2.60), pronunciation and fluency (1.57 to 2.37), and sentence accuracy and appropriateness (1.63 to 2.67). Notably, lower-proficiency students benefited most, with the low-level group showing an average gain of 27.85 points compared to 14.55 points for the high-level group. Student satisfaction was exceptionally high, with an overall mean score of 4.93 out of 5.00, indicating strong agreement across all dimensions including teaching content, learning activities, teacher performance, teaching methods, assessment, and overall satisfaction. Conclusion: The flipped classroom teaching method is highly effective in enhancing vocational college students’ Thai speaking skills for introducing tourist attractions and strengthens learner engagement. Its success stems from enhanced autonomous learning via pre-class videos, clearer goal orientation through context-specific content, and increased speaking practice with immediate in-class feedback. This model is particularly beneficial for lower-proficiency students and has high sustainability and scalability for oral Thai instruction in vocational education contexts, providing important practical value for optimizing vocational Thai speaking teaching.